1998
DOI: 10.1172/jci2029
|View full text |Cite
|
Sign up to set email alerts
|

Human blood-brain barrier receptors for Alzheimer's amyloid-beta 1- 40. Asymmetrical binding, endocytosis, and transcytosis at the apical side of brain microvascular endothelial cell monolayer.

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
162
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(174 citation statements)
references
References 48 publications
11
162
0
1
Order By: Relevance
“…• An imbalance between the production and clearance of amyloid-β (Aβ) is an early, often initiating, factor in Alzheimer disease (AD) • Peripheral systems are suggested to be involved in Aβ production and clearance • The central and peripheral pathways of Aβ metabolism communicate with each other, and work synergistically to clear Aβ from the brain • Increasing experimental, epidemiologic and clinical evidence suggests that AD manifestations extend beyond the brain, and that AD pathogenesis is closely associated with systemic abnormalities • The systemic abnormalities in patients with AD might not be secondary to the cerebral degeneration; instead, they might reflect underlying disease processes • A systemic view of AD provides a novel perspective for understanding the role of Aβ in AD pathogenesis and offers opportunities for the development of new treatments and diagnostic biomarkers for AD 29 . The arachnoid villi absorb Aβ in the CSF and mediate its release into the circulation 30 .…”
Section: Key Pointsmentioning
confidence: 99%
“…• An imbalance between the production and clearance of amyloid-β (Aβ) is an early, often initiating, factor in Alzheimer disease (AD) • Peripheral systems are suggested to be involved in Aβ production and clearance • The central and peripheral pathways of Aβ metabolism communicate with each other, and work synergistically to clear Aβ from the brain • Increasing experimental, epidemiologic and clinical evidence suggests that AD manifestations extend beyond the brain, and that AD pathogenesis is closely associated with systemic abnormalities • The systemic abnormalities in patients with AD might not be secondary to the cerebral degeneration; instead, they might reflect underlying disease processes • A systemic view of AD provides a novel perspective for understanding the role of Aβ in AD pathogenesis and offers opportunities for the development of new treatments and diagnostic biomarkers for AD 29 . The arachnoid villi absorb Aβ in the CSF and mediate its release into the circulation 30 .…”
Section: Key Pointsmentioning
confidence: 99%
“…75 These studies were expanded to demonstrate that RAGE was responsible for the influx of Ab across BBB. 76,77 Interaction of Ab and RAGE at the endothelial surface was shown to induce the production of pro-inflammatory cytokines and endothelin-1, a potent vasoconstrictor, thus reducing cerebral blood flow and potentially exacerbating AD pathology. 76 RAGE is implicated in AD pathogenesis not only through mediation of Ab influx across BBB, but also through inflammatory and pro-coagulant activity within the endothelium, production of reactive oxygen species and the induction of apoptosis through the nuclear factor-êB pathway.…”
Section: Influx Of Ab Rage/ab Interactions At Bbbmentioning
confidence: 99%
“…Although it is not yet clear which species of Aβ (soluble or insoluble) binds to RAGE (Yan et al ., 2009), the strong increase of RAGE in the high‐AGE diet group together with the significant correlation of insoluble Aβ 42 with AGEs intake suggests that insoluble Aβ binds to RAGE. This is consistent with the influx of Aβ across the BBB depending on its interaction with RAGE (Mackic et al ., 1998) and that it was shown that AGEs increase the amount of fibronectin in pericytes and directly induce hypertrophy at the BBB via RAGE signaling (Shimizu et al ., 2013). In addition, levels of AGEs were significantly higher (~twofold) in hippocampal insoluble Aβ fraction in the Tg2576 group on H‐AGE diet compared to the other three groups as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%